Characterization of Phenology and Growth Phases of Local Sorghum (Sorghum bicolor L. Moench) from East Sumba - Wati, Lita Wahyu Rika; Sari, Agnes Dwi Meita; Kurnia, Theresa Dwi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Sorghum is one of the cereal crops currently being widely developed as an alternative food in Indonesia. One of the approaches is through research in the field of plant breeding. To initiate the development of more advanced research, with future research focused on developing local cultivars as part of local wisdom that preserves sustainability and genetic diversity, information is needed regarding the phenological characteristics and growth phases of sorghum plants as conducted in this study. The plant materials used were two local sorghum genotypes of East Sumba, namely Watar Hammu Manippa Tadda and Watar Hammu Mitting Nggangga. A descriptive research method was used to provide a detailed description of the characteristics of sorghum plants. The research was conducted from June to December 2024 at the Science Techno Park (STP), Faculty of Agriculture and Business, Satya Wacana Christian University, Wates Village, Getasan District, Semarang Regency, at an altitude of 1118 meters above sea level. The results showed that the local East Sumba sorghum genotypes, Watar Hammu Manippa Tadda and genotype Watar Hammu Mitting Nggangga, have similar phenological charactersistics in terms of leaf, stem, and root, while their seed characteristics and panicle shapes of the two types are different, with clear distinctions in seed and panicle morphology serving as important differentiating traits. Based on the growth phase, there are no significant differences between the two genotypes. The research results indicates that both genotypes have strong potential as breeding materials, with breeding efforts best directed toward combining the superior traits of each genotype, maintaining local adaptation while improving seed productivity and quality. This study provides detailed information on the phenological characteristics and growth phases of two local sorghum varieties from East Sumba. Information related to plant phenology is an important foundation for developing sorghum breeding research in Indonesia. Knowing the characteristics of the plant also supports the optimal use of sorghum as a food source or alternative feed.